Eco-Africa and facilitated community participation in the /AI-/AIS Richtersveld Transfrontier Conservation Area - Classen Monique, Ann (Department of Environmental and Geographical Science, 2017)
This research investigates how environmental consultancies frame participation as a tool for project implementation using a cross-border conservation initiative as a case study. The study focuses on the facilitation process led by Eco-Africa Environmental Consultants during the establishment of the /Ai-/Ais Richtersveld Transfrontier Conservation Area. This study analyzes the promise of participation as a crucial component for Transfrontier Conservation Areas. Analyzing participation of the Richtersvelders is necessary for understanding the work that was carried out and how it was experienced by the stakeholders. The study refers to participation in conservancies in community-based resource management, where the role of non-government organizations and environmental consultancies is well established. Primary data were collected through qualitative document analysis, semi-structured interviews with members of the four communities and with Eco-Africa Environmental Consultants. The findings of the study are that there was a strong attempt towards an all-inclusive bottom-up approach to participation. However, such the success of such an approach was hampered by local mismanagement, politics of money, and a marketing strategy favoring the South African National Parks and the Transfrontier Conservation project.